Analisis Sistem Pengawasan MUI Terhadap Sertifikat Halal pada UMKM di Kota Surakarta - Purwanto; Suprihati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the role of the Indonesian Ulema Council (MUI) in supervising the halal certification process for Micro, Small, and Medium Enterprises (MSMEs) in Surakarta City. The research method used is descriptive qualitative, involving MSME actors, MUI Surakarta officers, and a number of related documents. The results of the study indicate that MUI has an important role in ensuring the halalness of products and increasing consumer confidence. Initially, halal certification was issued by MUI Surakarta, but now the authority has been transferred to the Halal Product Guarantee Organizing Agency (BPJPH) under the Ministry of Religion. However, MUI still has a role in supervision through its fatwas and monitoring of products in circulation. MSMEs in Surakarta face challenges in obtaining halal certification, such as limited resources and knowledge of certification procedures. However, halal certification not only benefits consumers, but also producers, because products with a halal label can increase customer trust and loyalty. The effectiveness of the MUI supervision system in Surakarta already has a strong foundation, but there is still a need for improvement, especially in facing the challenges of the digital era and dynamic regulatory changes. This study presents a new approach with a focus on the analysis of the MUI supervision system for halal certification of MSMEs in Surakarta based on product identification, type, nature, and characteristics. The final result is that the role of MUI in facilitating and supervising the halal certification process is very important to improve the effectiveness of supervision and facilitate MSME access to halal certification. This study provides valuable insights for policy makers and halal industry players in improving the effectiveness of supervision and facilitating MSME access to halal certification.